Limosilactobacillus fermentum KBL674 Alleviates Vaginal Candidiasis - Sung Jae Jang; Eun Jung Jo; Cheonghoon Lee; Bo-Ram Cho; Yun Jeong Shin; Jun Soo Song; Woon-Ki Kim; Nanhee Lee; Hyungjin Lee; SungJun Park; GwangPyo Ko (Probiotics and Antimicrobial Proteins, 2025)
Candida albicans ( C. albicans ) is the primary etiologic agent of vaginal candidiasis. Lactobacillus species are predominant in the vaginal microbiome; they inhibit the development of vaginal candidiasis by producing antimicrobial agents, such as lactic acid and hydrogen peroxide. In this study, we investigated the effects of Limosilactobacillus fermentum ( L. fermentum ) KBL674 in a mouse model of vaginal candidiasis. L. fermentum KBL674 inhibited C. albicans hyphal growth. Moreover, oral administration of L. fermentum KBL674 significantly suppressed vaginal C. albicans infection and associated symptoms, including tissue thickness and immune cell infiltration. A substantial quantity of L. fermentum KBL674 was excreted by the mice within 6 h after oral administration, indicating that most L. fermentum KBL674 did not settle within the gastrointestinal tract. L. fermentum KBL674 modulated gut microbiome diversity, increasing abundances of the genera Akkermansia , Eubacterium , and Faecalibaculum and family Muribaculaceae . Abundances of these bacteria showed negative correlations with the vaginal C. albicans burden in the mouse model, suggesting links between the gut microbiome composition and the vaginal C. albicans burden . Therefore, L. fermentum KBL674 can reduce the vaginal C. albicans burden via direct or indirect inhibition and modulation of the gut microbiome composition preventively. Graphical Abstract